RESPON TANAMAN GAMAL (Gliricidia sepium) DAN INDIGOFERA (Indigofera zollingeriana) TERHADAP PEMBERIAN PUPUK ANORGANIK DAN ORGANIK - Roni N.G.K.; S.A. Lindawati (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
The productivity of forage depends on the availability of nutrients in the soil where it is grown, so fertilization to replace harvested produce is absolutely necessary. This study aims to study the response of gamal and indigofera forage on application of inorganic and organic fertilizers. Research using a completely randomized design factorial pattern of two factors, the first factor is the type of plant (G = Gamal; I = Indigofera) and the second factor is the type of fertilizer (T = without Fertilizer; A = Inorganic fertilizer NPK; K = commercial organic fertilizer; O = conventional organic fertilizer; B = bioorganic fertilizer), repeated 4 times so that it consists of 40 experimental units. The variables observed were plant height, number of leaves, stem diameter, leaf dry weight, stem dry weight, total dry weight of leaves, ratio of dry weight of leaves/stems and leaf area per pot. The results showed that there was no interaction between plant species and types of fertilizer in influencing the response of gamal and indigofera plants. Plant species have a significant effect on stem diameter, while fertilizer types have a significant effect on plant height, leaf dry weight, total dry weight of leaves and leaf area per pot. Based on the results of the study it can be concluded that the response of gamal plants is similar to indigofera, all types of fertilizers can improve the response of plants and organic fertilizers produce the same crop response with inorganic fertilizers. Keywords: gamal, indigofera, inorganic fertilizer, organic fertilizer